MANAJEMEN PERSAMPAHAN DAN PROGRAM 3R (REDUCE, REUSE DAN RECYCLE) - Harapan Tua, Frinda Novita, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Solid Waste Management and 3R Program (Reduce, Reuse and Recycle). This study aims to find out and analyze waste management in a 3R program case study in Pebatuan Village, Tenayan Raya District, Pekanbaru City. This type of research is a qualitative approach with methods of observation, interviews and documentation. The informants in this study were the people who participated in this 3R program. The method of data analysts uses non statistical analysis techniques or commonly referred to as logical analysis. The results of this study indicate that waste management using the 3R program has not run optimally due to the lack of socialization related to the 3R program in the Pebatuan Sub-District of Tenayan Raya District, lack of budget to support the garbage bank program, lack of technical training related to the 3R program, facilities and infrastructure of waste banks which is inadequate.